A Qualitative Approach to Understand Key Components of Independent Film Production Companies’ Business Model in the European Film Market - Vitkauskaitė, Ieva (Information & Media, 2025)
The purpose of this study is to better understand what components of business models independent film production companies in Europe use to compete in the European film market using empirical data from multiple countries. It provides an analysis of independent film production companies’ business model components which are comprised of the elements ‘Value creation’, ‘Value proposition’, and ‘Value capture’. The empirical study was implemented by using purposive sampling. The participants included 17 experts from 8 European countries with direct links to practical management of a film production company who are denoted by comprehensive experience within the European film industry as well as the business models used by independent film production companies. Thematic analysis of the semi-structured interviews identified 11 categories encompassing 60 sub-categories.By using the results of the empirical research study, a model has been created to show the relationship of components and sub-constructs that make independent film production companies competitive in the market. Two critical components were identified in the research that independent film production companies need to focus on. They include outstanding talent as one of the key components of the business model and stakeholders/investment partners. The study has also revealed challenges that include slow funding systems based on subsidies. The results of the study thus shed light on the general situation for independent film production companies, and form a foundation for future studies in this area. The article was written based on a dissertation in progress.
Keywords: business model; film production; independent film production company; film production company; European film market; film industry